2021
DOI: 10.7759/cureus.18570
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Suicidal Patterns in the Emergency Room: A Clinical and Social Reflection

Abstract: Background and objectiveEmergency physicians come across a myriad of medical afflictions resulting from suicide attempts. The Indian contribution to global suicide deaths is alarming; the social construct of India is unique, and so are the problems and challenges. This study aims to describe the social background, demographic parameters and correlate the clinical profile and outcomes of all patients presenting with an attempted or completed suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In prior research, a gender disparity has been observed in the frequency of self-harm attempts, with women reporting a higher number of attempts than men [5,6,9,22,25,26,36]. No correlation was identified between relationship status and drug use across the two periods under study, although such a relationship is evident in the context of psychiatric history and treatment.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In prior research, a gender disparity has been observed in the frequency of self-harm attempts, with women reporting a higher number of attempts than men [5,6,9,22,25,26,36]. No correlation was identified between relationship status and drug use across the two periods under study, although such a relationship is evident in the context of psychiatric history and treatment.…”
Section: Discussionmentioning
confidence: 87%
“…No correlation was identified between relationship status and drug use across the two periods under study, although such a relationship is evident in the context of psychiatric history and treatment. Current evidence suggests that confinement in isolation and uncertainty can have negative consequences, leading to an increase in mental health problems such as anxiety and depression [9,11,19,20,25]. In contrast, a study conducted in the Czech Republic found that the happiness and quality of life of individuals during the peak of the pandemic was higher than that measured one year before the pandemic.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation